1983
DOI: 10.2307/3897978
|View full text |Cite
|
Sign up to set email alerts
|

Beef Cattle Performance on Crested Wheatgrass Plus Native Range vs. Native Range Alone

Abstract: Cattle gains and conception rates in 1974-1977 on crested wbeatgrass pasture in spring and fall and native range in summer (CW-NR system) were compared with performance on native range throughout the grazing season (NR system). The CW-NR and NR systems were stocked at 0.20 and 0.10 AU/ha, respectively. Conception rates on CW-NR and NR were 84% and 86%, respectively, excluding results from 1975 when there were problems with heat detection; this difference was not significant. Cow, heifer, and calf gains (averag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
15
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 8 publications
5
15
0
Order By: Relevance
“…Data from this study and others clearly show that seeded pastures can provide more forage than native rangeland (Smoliak 1968;Hart et al 1983;Adams et al 1989) and will support increased grazing pressure in spring and autumn. However, this may not occur every year or with every seeded species (Willms and Jefferson 1993).…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations
“…Data from this study and others clearly show that seeded pastures can provide more forage than native rangeland (Smoliak 1968;Hart et al 1983;Adams et al 1989) and will support increased grazing pressure in spring and autumn. However, this may not occur every year or with every seeded species (Willms and Jefferson 1993).…”
Section: Discussionsupporting
confidence: 50%
“…Some report increased individual animal performance from grazing seeded pastures (Houston and Urick 1972) whereas others report the main advantage to be associated with increased seasonal carrying capacity (Hart et al 1983;Adams et al 1989;Hofmann et al 1993). We observed both increased animal performance and potential increases in spring and autumn carrying capacity with seeded pastures during most years of this study.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…For example, past research in the northern plains region has suggested a potential role of controlled grazing for improving vegetation productivity, changing plant species composition, increasing diversity, and/or accelerating carbonnutrient cycling and pedogenesis (DePuit andCoenen berg 1989, Young andRennick 1983) . Furthermore, animal performance while grazing revegetated mined lands may provide one important indication of reclamation success from the standpoint of grazing utility (Sindelar andMurdock 1985, Ries andHofmann 1984).…”
Section: Introductionmentioning
confidence: 99%